Amrubicin and carboplatin with pegfilgrastim in patients with extensive stage small cell lung cancer: A phase II trial of the Sarah Cannon Oncology Research Consortium. (March 2018) - Spigel, David R.; Hainsworth, John D.; Shipley, Dianna L.; Mekhail, Tarek M.; Zubkus, John D.; Waterhouse, David M.; Daniel, Davey B.; Burris, Howard A.; Greco, F. Anthony
Highlights: The amrubicin/carboplatin combination was active as 1st-line therapy for SCLC. The median survival (10 months) did not suggest any advantage vs. standard regimens. Despite prophylactic pegfilgrastim, severe myelosuppression was common. Abstract: Purpose: First-line treatment for patients with extensive-stage small cell lung cancer (SCLC) includes treatment with platinum-based combination chemotherapy. Amrubicin is a synthetic anthracycline with single-agent activity in relapsed/refractory SCLC. In an attempt to improve treatment efficacy, we evaluated amrubicin/carboplatin as first-line therapy for extensive-stage SCLC. Patients and methods: In this multicenter phase II trial, patients received amrubicin (30 mg/m 2 daily on Days 1, 2, and 3) and carboplatin (AUC = 5 on Day 1); cycles were repeated every 21 days for 4 cycles. Pegfilgrastim (6 mg subcutaneously) was administered on Day 4 of all cycles. Overall survival (OS) proportion at 1 year was the primary endpoint. The target 1-year OS rate was 47%, an improvement of 35% from historical results with carboplatin/etoposide. Results: Eighty patients received study treatment, and 62% completed the planned 4 courses. The overall response rate was 74% (13% complete responses). The 1-year survival rate was 38% (95% CI: 25, 50). The median survival was 10 months. Myelosuppression was severe but manageable. Conclusions: The combination of amrubicin/carboplatin was an active first-line treatment for extensive stage SCLC, but showed no indication of increased efficacy compared to standard treatments. Severe myelosuppression was common with this regimen, in spite of prophylactic pegfilgrastim. These results are consistent with those of other trials in showing no role for amrubicin in the first-line treatment of SCLC.